Synthesis and antitumor activity of 5-(5-halogenated-2-oxo-1H-pyrrolo[2, 3-b]pyridin-(3Z)-ylidenemethyl)-2, 4-dimethyl-1H-pyrrole-3-carboxamides. Issue 14 (15th July 2015) - Wang, Minghua; Ye, Cheng; Liu, Mingliang; Wu, Zhaoyang; Li, Linhu; Wang, Chunlan; Liu, Xiujun; Guo, Huiyuan
Graphical abstract A series of 5-halogenated-7-azaindolin-2-one derivatives were synthesized. Compound 13c7 were found to be more active than Sunitinib against all of the tested cancer cell lines.